2016
DOI: 10.1038/srep21206
|View full text |Cite
|
Sign up to set email alerts
|

Non-canonical features of the Golgi apparatus in bipolar epithelial neural stem cells

Abstract: Apical radial glia (aRG), the stem cells in developing neocortex, are unique bipolar epithelial cells, extending an apical process to the ventricle and a basal process to the basal lamina. Here, we report novel features of the Golgi apparatus, a central organelle for cell polarity, in mouse aRGs. The Golgi was confined to the apical process but not associated with apical centrosome(s). In contrast, in aRG-derived, delaminating basal progenitors that lose apical polarity, the Golgi became pericentrosomal. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
66
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 79 publications
9
66
0
Order By: Relevance
“…The formation of cell processes, such as neurites, and the establishment of cell polarity are closely associated with microtubule organization that takes place at the microtubule‐organizing center, including the centrosome, located at the base of cell processes (Taverna et al, ; Wiese & Zheng, ). To confirm the polarity changes of RGL cells, the expression of γ‐tubulin, a centrosome marker (Taverna et al, ; Wiese & Zheng, ) was analyzed in Gfap ‐GFP+/S100β− cells at 10 days after pilocarpine injection. The angle α between the nucleus‐centrosome axis (centrosomes were visualized as γ‐tubulin+ puncta) and the inferior border of the GCL was measured (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…The formation of cell processes, such as neurites, and the establishment of cell polarity are closely associated with microtubule organization that takes place at the microtubule‐organizing center, including the centrosome, located at the base of cell processes (Taverna et al, ; Wiese & Zheng, ). To confirm the polarity changes of RGL cells, the expression of γ‐tubulin, a centrosome marker (Taverna et al, ; Wiese & Zheng, ) was analyzed in Gfap ‐GFP+/S100β− cells at 10 days after pilocarpine injection. The angle α between the nucleus‐centrosome axis (centrosomes were visualized as γ‐tubulin+ puncta) and the inferior border of the GCL was measured (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed whether a given transcript is translated could be related to a number of factors including mRNA reporter, RGC cell cycle stage, developmental stage, or signals emanating from surrounding niche. Beyond local translation at endfeet, it is interesting to consider that within basal processes, translation ‘hot spots’ may also exist, as suggested by a recent study which showed ER are scattered along the basal process .…”
Section: Live Imaging: Rna and Rna‐binding Proteins Move And Functionmentioning
confidence: 99%
“…The FMRP interactome at basal endfeet also contains some mRNAs encoding membrane and secreted proteins. However, use of both EM and fluorescent proteins marking Golgi components, indicate that RGC basal processes and endfeet lack conventional golgi apparatus, as do neuronal axons . This raises the question of how some locally translated proteins are appropriately modified in the absence of Golgi.…”
Section: Live Imaging: Rna and Rna‐binding Proteins Move And Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being highly polarized, these cells also display asymmetric localization of cellular processes, cellular components and molecules. For example, the Golgi apparatus are preferentially localised at the apical process, while the endoplasmic reticulum is localised in both the apical and basal processes .…”
Section: Morphological Diversitymentioning
confidence: 99%